Slope stability analysis considering weight of trees and root reinforcement - Lotfalian, Majid; Nasiri, Mehran; Modarres, Amir; Wu, Wei (Journal of Environmental Engineering and Landscape Management, 2019)
We study the effect of roots of alder trees on soil reinforcement and slope stabilization. Two types of soil, i.e. Marl and Clayey soils and alders of three ages are considered. The slope stability is studied according to the tree indices based on tree age and soil type. The effect of root reinforcement on slope stability is considered by an additional cohesion. The stability analyses are carried out by the FEM. We perform parameter studies considering tree age, soil type and surcharge. The results indicate that soil type is effective on cohesion. The results also showed that with increasing age of trees from 7 to 15 years, the amount of additional root cohesion increased and with the increase of the age of trees to 20 years this amount slightly decreased. Also, with regard to a constant slope geometry, the type of soil and the uniform surcharge pressure, 7-year-old trees have shown better performance in slope stabilization. It has been observed that as the age of alder trees grows, although the amount of additional root cohesion increases, however, due to increased surcharge pressure, the overall slope stability factor decreases.